Development of Small-Diameter Elastin-Silk Fibroin Vascular Grafts - Tanaka, Takashi; Abe, Yasuyuki; Cheng, Chieh-Jen; Tanaka, Ryo; Naito, Akira; Asakura, Tetsuo (Frontiers in Bioengineering and Biotechnology, 2021)
Globally, increasing mortality from cardiovascular disease has become a problem in recent years. Vascular replacement has been used as a treatment for these diseases, but with blood vessels less than 6 mm in diameter, existing vascular grafts made of synthetic polymers can be occluded by thrombus formation or intimal hyperplasia. Therefore, the development of new artificial vascular grafts is desirable. In this study, we developed an elastin (EL)–silk fibroin (SF) double-raschel knitted vascular graft 1.5 mm in diameter. Water-soluble EL was prepared from insoluble EL by hydrolysis with oxalic acid. Compared to SF, EL was less likely to adhere to platelets, while vascular endothelial cells were three times more likely to adhere. SF artificial blood vessels densely packed with porous EL were fabricated, and these prevented the leakage of blood from the graft during implantation, while the migration of cells after implantation was promoted. Several kinds of 13C solid-state NMR spectra were observed with the EL–SF grafts in dry and hydrated states. It was noted that the EL molecules in the graft had very high mobility in the hydrated state. The EL–SF grafts were implanted into the abdominal aorta of rats to evaluate their patency and remodeling ability. No adverse reactions, such as bleeding at the time of implantation or disconnection of the sutured ends, were observed in the implanted grafts, and all were patent at the time of extraction. In addition, vascular endothelial cells were present on the graft’s luminal surface 2 weeks after implantation. Therefore, we conclude that EL–SF artificial vascular grafts may be useful where small-diameter grafts are required.